(untitled) (Al-Academy, 2026)
When art has become a necessity in our lives, it solves problems and sometimes provides solutions to them. The forms of art have multiplied and expanded, but the goal remains the same, dominated by the human character, and we, as recipients, distinguish art on several levels in terms of quality, mastery of work, and reaching a human goal that touches the soul and expresses our lives. Style has emerged in art as a characteristic that distinguishes its maker. When the name of any international director is mentioned, his style that distinguishes him from others comes to mind. On this basis, the researcher set out to define the topic of his research: Stylistic Characteristics of Director Asghar Farhadi.